If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -3(6z + 5) = -4(-1z + 7) + -6 Reorder the terms: -6 + -3(5 + 6z) = -4(-1z + 7) + -6 -6 + (5 * -3 + 6z * -3) = -4(-1z + 7) + -6 -6 + (-15 + -18z) = -4(-1z + 7) + -6 Combine like terms: -6 + -15 = -21 -21 + -18z = -4(-1z + 7) + -6 Reorder the terms: -21 + -18z = -4(7 + -1z) + -6 -21 + -18z = (7 * -4 + -1z * -4) + -6 -21 + -18z = (-28 + 4z) + -6 Reorder the terms: -21 + -18z = -28 + -6 + 4z Combine like terms: -28 + -6 = -34 -21 + -18z = -34 + 4z Solving -21 + -18z = -34 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. -21 + -18z + -4z = -34 + 4z + -4z Combine like terms: -18z + -4z = -22z -21 + -22z = -34 + 4z + -4z Combine like terms: 4z + -4z = 0 -21 + -22z = -34 + 0 -21 + -22z = -34 Add '21' to each side of the equation. -21 + 21 + -22z = -34 + 21 Combine like terms: -21 + 21 = 0 0 + -22z = -34 + 21 -22z = -34 + 21 Combine like terms: -34 + 21 = -13 -22z = -13 Divide each side by '-22'. z = 0.5909090909 Simplifying z = 0.5909090909
| 2(y+5)3=y+2 | | 3(2x-5)=4(x+3) | | x^2-12x+117=0 | | 7(x-4)=7(8-2x)+21x | | x^5-5x^3+4x+2=0 | | x+1.8=-1.4 | | x+25+2x=-6-2x-9 | | 17.2=-21.2+6u | | 3x-6=2x-2 | | 8v+7=-2v+7 | | v=lmh | | y-3=x+2 | | 10x+2=2(5x+1) | | 3(x+4)-5x=-4(x-3)+2x | | 6.4=x-3.7 | | 5y-9=3(y-5) | | 2v+8=-4 | | 5x-9=3(y-5) | | -2.7x-2.7=-2.1x-2.1 | | 16-4x=9+3x | | 2G+12=24 | | 3x^2+16x-209=0 | | 32x+42y=30x+70y | | 5x+8=7x-10 | | 32x+48y=1 | | -1.6z+3=-5 | | 5.4=x+3.7 | | 0=3v+18 | | 26+x=24 | | 5u-3=-10 | | -11x=15 | | -9w+3=0 |